Efficacy of Jinhua Qinggan Granules Combined With Western Medicine in the Treatment of Confirmed and Suspected COVID-19: A Randomized Controlled Trial - An, XueDong; Xu, Xi; Xiao, MingZhong; Min, XiaoJun; Lyu, Yi; Tian, JiaXing; Ke, Jia; Lang, SuPing; Zhang, Qing; Fan, An; Liu, BinBin; Zhang, Ying; et al. (Frontiers in Medicine, 2021)
Objective To conduct a randomized controlled clinical trial to evaluate the clinical efficacy and prognostic value of Jinhua Qinggan granules in patients with confirmed and suspected coronavirus disease 2019 (COVID-19). Methods A total of 123 suspected and confirmed COVID-19 patients participated in this clinical trial and were randomly divided into Jinhua and Western medicine groups. For 14 days, the Jinhua group was treated with Jinhua Qinggan granules and antiviral drugs, and the Western medicine group was treated with antiviral drugs alone. We collected information on clinical symptoms, disease aggravation rates, and negative conversion rates of nucleic acids in patients, and observed the effects of anti-infective drugs. Results: There was no significant difference in symptom improvement rates between the two groups, both confirmed and suspected patients (P > 0.05). Both treatments relieved symptoms such as fever, fatigue, and diarrhea. However, the Jinhua treatment was superior in relieving fever and poor appetite. Anti-infective drug use rates were significantly lower in the Jinhua group than in the control group. Conclusion Jinhua Qinggan granules combined with Western medicine could relieve the clinical symptoms of fever and poor appetite in COVID-19 patients, reduce the use of antibiotics to a certain extent.